FAKTOR-FAKTOR YANG MEMPENGARUHI VOLATILITAS HARGA SAHAM PERUSAHAAN PUBLIK SEKTOR ASURANSI - Wulandari, Endang; Septiani, Mira (Journal Economics Technology And Entrepreneur, 2025)
This study aims to analyze the factors that influence the stock price volatility of publicly listed insurance companies on the Indonesia Stock Exchange (IDX) during the period of 2020-2024. This research employs quantitative methods, and it explains the effect of independent variables such as leverage, asset growth, and company size on the dependent variable which is stock price volatility. The population and sample for this study comprise 18 companies. The data used in this research are secondary data, and the data analysis technique employs a panel data regression model with the help of Eviews 11 software. The research results show that, partially, the asset growth variable has a significant effect on stock price volatility, while the leverage and company size variables have no significant effect on stock price volatility. Simultaneously, the independent variables, namely leverage, asset growth, and company size, collectively have a significant effect on the dependent variable of stock price volatility.